2009
DOI: 10.1183/09031936.00106008
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial hypertension in limited cutaneous systemic sclerosis: a distinctive vasculopathy

Abstract: Systemic sclerosis-associated pulmonary arterial hypertension (SScPAH) has a worse prognosis and response to pulmonary arterial hypertension (PAH) therapy than idiopathic PAH (IPAH). These differences have not yet been explained. Knowledge concerning histological pulmonary vasculopathy in SScPAH is limited in contrast to IPAH. Therefore, we explored patterns of vasculopathy in SScPAH compared with IPAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
115
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(124 citation statements)
references
References 56 publications
6
115
2
1
Order By: Relevance
“…As expected, there was a marked difference in survival between the three most common forms of group 1 (Eisenmenger's, IPAH and PAH-CTD), probably related to differences in demographic characteristics such as age, in the ability of the right ventricle to cope with increased afterload and in the severity of the underlying pulmonary vasculopathy [27,28]. In the CTEPH group, patients with operable disease who underwent PEA had the best long-term outcome, confirming the importance of appropriate operative intervention.…”
Section: Discussionmentioning
confidence: 88%
“…As expected, there was a marked difference in survival between the three most common forms of group 1 (Eisenmenger's, IPAH and PAH-CTD), probably related to differences in demographic characteristics such as age, in the ability of the right ventricle to cope with increased afterload and in the severity of the underlying pulmonary vasculopathy [27,28]. In the CTEPH group, patients with operable disease who underwent PEA had the best long-term outcome, confirming the importance of appropriate operative intervention.…”
Section: Discussionmentioning
confidence: 88%
“…As an inadequate response to first-line PAH medical treatments is frequently observed in PVOD patients [1], it is likely that a significant proportion of patients showing insufficient response to first-line PAH therapy could be candidates for sequential add-on combination therapy and that such a strategy might increase the risk of developing pulmonary oedema. This eventuality may be more likely in scleroderma patients, who are prone to present with significant pulmonary venous involvement [4]. We report a case of severe pulmonary oedema occurring in a scleroderma patient with PVOD who was offered sequential combination therapy with sildenafil in a goal-oriented strategy after inadequate response to first-line bosentan.…”
Section: To the Editorsmentioning
confidence: 97%
“…PVOD is usually considered to represent 5-10% of patients initially diagnosed with ''primary'' (idiopathic) pulmonary hypertension [1]. It is believed to be even more common in patients with scleroderma-associated pulmonary hypertension [1,4]. A better understanding of different clinical presentation and outcomes in PVOD patients [1,5] has led to a recent update of the pulmonary hypertension classification [6].…”
Section: To the Editorsmentioning
confidence: 99%
“…In addition, high-resolution computed tomography of the chest can be suggestive of PVOD in the presence of centrilobular groundglass opacities, septal lines, and lymph node enlargement (67). Two recent histological studies suggested that SSc-PAH may be characterized by a more frequent involvement of pulmonary veins than previously recognized, perhaps explaining in part why these patients are less responsive to specific PAH treatment as compared with patients with IPAH (26,68). Lung transplantation remains the only suitable alternative for most patients with PVOD.…”
Section: Pulmonary Venoocclusive Diseasementioning
confidence: 99%